2015
DOI: 10.1177/1534734614568375
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Skin Autofluorescence and Vascular Complications in Chinese Patients With Diabetic Foot Ulcer

Abstract: The tissue accumulation of advanced glycation end products (AGEs) can be noninvasively assessed as skin autofluorescence (SAF) by the AGE Reader(TM) device. We aimed to detect the association between SAF and diabetes-associated vascular complications in diabetic foot ulcer (DFU) patients engaged in this study. This cross-sectional survey consisted of 118 consecutive hospitalized diabetic foot patients. The diabetic microvascular (retinopathy, nephropathy, and neuropathy) and macrovascular referring to coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
4
19
1
Order By: Relevance
“…The differences in the prevalence in DR between the two studies could be caused in part by differences in DFU severity, as our study included patients with higher DFU grades (grades 4 and 5). Jiang et al[18] and Liu et al[19] reported the prevalence of DR as 40.9% and 21.2%, respectively, in patients with DFU; however, both studies involved younger patients with shorter diabetes durations than in our study. Another difference was that in these two studies, serum creatinine levels were 0.91 and 0.76 mg/dL, respectively, which were lower than that in our study (3.0 mg/dL).…”
Section: Discussioncontrasting
confidence: 63%
“…The differences in the prevalence in DR between the two studies could be caused in part by differences in DFU severity, as our study included patients with higher DFU grades (grades 4 and 5). Jiang et al[18] and Liu et al[19] reported the prevalence of DR as 40.9% and 21.2%, respectively, in patients with DFU; however, both studies involved younger patients with shorter diabetes durations than in our study. Another difference was that in these two studies, serum creatinine levels were 0.91 and 0.76 mg/dL, respectively, which were lower than that in our study (3.0 mg/dL).…”
Section: Discussioncontrasting
confidence: 63%
“…AGEs have been shown to be elevated in the serum of type 2 diabetic patients with PAD, with a simultaneous reduction in antioxidant status (Lapolla et al 2007). Other studies have used skin autofluorescence (SAF) as a non-invasive measurement of tissue AGE accumulation, and SAF has been reported to be significantly increased in PAD patients (Noordzij et al 2012;Liu et al 2015a;de Vos et al 2016). Additionally, in a 5-year prospective cohort study, higher SAF was independently associated with increased risk for all-cause mortality and fatal or nonfatal major adverse cardiovascular events (de Vos et al 2014), and SAF was a predictor for amputation in patients with PAD independent from the presence of DM and Fontaine stage (de Vos et al 2015).…”
Section: Agesmentioning
confidence: 99%
“…Most publications reporting other ethnic groups included East Asian subpopulations, predominantly from Japan or China 31 42 43. Therefore, it is essential to assess SAF levels in dark skinned subjects since they are the most prevalent skin type of the world and represent the group with highest incidence of diabetes 44.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%